Complexes of gold and imidazole formed in helium nanodroplets. Issue 11 (2nd March 2018) - Gatchell, Michael; Goulart, Marcelo; Kranabetter, Lorenz; Kuhn, Martin; Martini, Paul; Rasul, Bilal; Scheier, Paul
Abstract : We have studied complexes of gold atoms and imidazole (C3 N2 H4 ) produced in helium nanodroplets. Abstract : We have studied complexes of gold atoms and imidazole (C3 N2 H4, abbreviated Im) produced in helium nanodroplets. Following the ionization of the doped droplets we detect a broad range of different Au m Im n + complexes, however we find that for specific values of m certain n are "magic" and thus particularly abundant. Our density functional theory calculations indicate that these abundant clusters sizes are partially the result of particularly stable complexes, e.g. AuIm2 +, and partially due to a transition in fragmentation patterns from the loss of neutral imidazole molecules for large systems to the loss of neutral gold atoms for smaller systems.